An oxidovanadium(IV) complex with 4, 4′-di-tert-butyl-2, 2′-bipyridine ligand: Synthesis, structure and catalyzed cyclooctene epoxidation. (1st February 2020) - Fomenko, Iakov S.; Vincendeau, Sandrine; Manoury, Eric; Poli, Rinaldo; Abramov, Pavel A.; Nadolinny, Vladimir A.; Sokolov, Maxim N.; Gushchin, Artem L.
Graphical abstract: A new oxidovanadium(IV) complex has been synthesized and fully characterized. It catalyzes the oxidation of cyclooctene with tert -butyl hydroperoxide in chloroform. Abstract: The interaction of vanadium(III) chloride (VCl3 ) with 4, 4′-di- tert -butyl-2, 2′-bipyridine (dbbpy) in air resulted in the monomeric oxidovanadium(IV) complex [VOCl2 (dbbpy)(H2 O)] (1 ) in high yield. The complex was characterized by IR and EPR spectroscopies, by elemental analysis, and by single crystal X-ray diffraction analysis. The vanadium atom has a distorted octahedral coordination environment. The EPR spectrum of 1 in CH2 Cl2 demonstrates an eight-line signal typical of vanadium(IV) with a d 1 electronic configuration. Complex 1 exhibits catalytic activity in the cyclooctene oxidation with tert -butyl hydroperoxide (TBHP) in CHCl3 . Detailed EPR, NMR and GC–MS studies of the reaction revealed a few mechanistic details and the nature of by-products that are generated by involvement of the chloroform solvent.